Voucher system and school effectiveness: Reassessing school performance difference and parental choice decision-making - Carrasco, Alejandro; San Martín, Ernesto (Estudios de Economía, 2012)
This paper discusses the potential contribution of employing school effectiveness methodological approach within the ongoing research debate on school choice issues. Using the first approach, we estimate the effectiveness of a sample of Chilean schools after controlling by a baseline at the student level. In order to avoid the endogeneity of such a baseline with respect to the school effect, we use a longitudinal data set (SIMCE 2004 and SIMCE 2006) from which a natural pseudo-experiment is defined in such a way that the baseline is by design uncorrelated with the school effect. Thereafter, we investigate possible relationships between parental school choice (as declared in public standardized surveys) and the schools classified by their effectiveness. The main conclusions of this paper are, on the one hand, that there is not remarkable difference between municipal (public) and subsidised schools in terms of their effectiveness analyzed under value-added; and, on the other hand, that there is no relation between parental school choice preferences and school effectiveness.